Management of high inguinal undescended testis: a review of literature - K. Shreyas; Kirtikumar J. Rathod; Arvind Sinha (SpringerOpen, 2021)
Abstract Background Undescended testis is one of the most common paediatric surgical diagnoses. A lot of research has been done to date, to standardise the surgical management of intra-abdominal and extra-abdominal undescended testis. High inguinal undescended testis is a unique clinical encounter which demands additional surgical measures over conventional orchidopexy for better surgical results. Main body of abstract Open inguinal orchidopexy is a routine and quite straightforward operation for the majority of extra-abdominal undescended testis. However, there are instances in which the testis, even though situated in the inguinal region, poses a challenge for surgeons, to bring it in the scrotum by routine open inguinal orchiopexy. High inguinal testis can be defined as "any intra-canalicular testis present higher up in the inguinal canal and cannot be brought down easily to the scrotum by routine surgery as in standard orchiopexy (open or laparoscopy) and require additional lengthening manoeuvres". It needs additional surgical lengthening manoeuvres like Prentiss, along with the steps of routine orchiopexy to bring it down in the scrotum. This review article describes the various nomenclatures of undescended testis, appropriate investigations and also various additional surgical measures in the management of difficult high inguinal testis. Conclusion High inguinal undescended testis poses a unique technical challenge even to well-experienced surgeons. It is very important that surgeons dealing with this condition are well aware of the anatomy in this region and also various different manoeuvres described to date to bring the testis down in the scrotum.